IDEOLOGICAL DOCTRINE OR FALSE NEUTRALITY IN THE PROCESS OF INITIAL TEACHER TRAINING? INTERLOCATIONS WITH HISTORICAL-DIALETIC MATERIALISM - Francisco, Marcos Vinicius; Ponce, Rosiane de Fatima [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2020)
The present theoretical essay assumed as a general objective to analyze the contradictions of the School Without Party Law Project and the alleged pseudo-neutrality in the initial teacher training processes. The theoretical framework used is based on epistemological historical-dialectical materialism. The results revealed that both the Escola Sem Partido Movement, materialized by conservative segments of society, and the aforementioned Bill, in the name of seeking a possible neutrality in the dissemination of knowledge and combating discourses deviating from morals and good customs in school institutions only depoliticize educational action and concern the maintenance of current social relationships.
Keywords: School Without Party; Ideology; Initial Teacher Training